Insights Into Energy Accumulation and Allocation Strategy of Reproductive Migration of Black Amur Bream (Megalobrama terminalis) in the Pearl River Basin, China - Liu, Yaqiu; Li, Xinhui; Li, Jie; Li, Yuefei (Frontiers in Ecology and Evolution, 2022)
Energy allocation is an important component of the reproductive cycle, and as such it will affect survival, migration and reproductive success. To reduce the risk of reproductive migration failure and to optimally allocate a limited amount of energy, it is vital to first understand the trade-off between reproduction and somatic growth in migrating fish. In the current study, we chose Megalobrama terminalis, an endemic species residing in the Pearl River basin with relatively high migratory potential, as a candidate to investigate energy accumulation and allocation strategy during reproductive migration. The analysis used a quantitative assessment of biochemical composition and energy density in somatic and visceral tissues of M. terminalis females during the reproductive cycle. The results indicated that stage III to IV of M. terminalis was the vital migration-launching period. The asynchrony of development was confirmed in energetic relationships in muscle and ovary. Specifically, there was a regulatory mechanism for allocating lipids to each tissue reasonably during the breeding migratory preparation period (stage III). The significant change in lipid content of the ovary is considered as a crucial physiological index reflecting the readiness for breeding migration of M. terminalis. In addition, the negative energy density relationship between somatic and reproductive tissues indicated a trade-off between maximum metabolic ability and energy efficiency before migration-launching in M. terminalis. The present findings provide effective information for initiating further research of on the ecological adaptation of migrating fish species.